2015
DOI: 10.1136/annrheumdis-2015-207838
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment with biologic DMARDs on the risk of sepsis or mortality after serious infection in patients with rheumatoid arthritis

Abstract: ObjectiveThis observational cohort study investigated the impact of biological (b) disease-modifying antirheumatic drugs (DMARDs) on the outcomes of serious infections (SIs) in patients with rheumatoid arthritis.MethodsWe investigated outcomes of SIs observed in 947 patients enrolled in the German biologics register RABBIT(Rheumatoid arthritis: observation of biologic therapy). Outcomes were (1) recovery without complication, (2) sepsis following SI (≤30 days), and (3) death after SI without known sepsis (≤90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
1
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 31 publications
0
79
1
8
Order By: Relevance
“…It was interesting to observe that a lower rate of sepsis was seen with the anti-TNF drugs compared with rituximab. Previous work from the German RABBIT register found that the risk of developing sepsis among individuals with SI and mortality from sepsis was lower with anti-TNF therapy compared with non-biologic DMARDs 16. This is perhaps not surprising as TNF is thought to be an important cytokine in the development of sepsis and clinical trials have been carried out to evaluate the use of TNF blockade in treating patients with severe sepsis 17 18.…”
Section: Discussionmentioning
confidence: 98%
“…It was interesting to observe that a lower rate of sepsis was seen with the anti-TNF drugs compared with rituximab. Previous work from the German RABBIT register found that the risk of developing sepsis among individuals with SI and mortality from sepsis was lower with anti-TNF therapy compared with non-biologic DMARDs 16. This is perhaps not surprising as TNF is thought to be an important cytokine in the development of sepsis and clinical trials have been carried out to evaluate the use of TNF blockade in treating patients with severe sepsis 17 18.…”
Section: Discussionmentioning
confidence: 98%
“…Compared to the general population, the increased susceptibility of CTD patients to infections is related to three main parameters: (a) intrinsic immunological abnormalities associated with the mater CTD; (b) chronic specific CTD-related lung involvement such as bronchiectasis and fibrotic ILDs, both constituting hosts to an altered human microbiome, and (c) clinically significant immunological dysfunction induced by the use of synthetic and biological disease-modifying drugs [4,29,54,55,56]. Increased age and digestive tract involvement, predisposing to aspiration as in DM-PM and scleroderma, further aggravate the risk [25].…”
Section: Acute Lung Infections In Ctdsmentioning
confidence: 99%
“…In addition, acute respiratory events may precipitate disease-specific extrapulmonary organ involvement such as aspiration pneumonia as well as the far less frequently occurring Mendelson syndrome with digestive tract involvement, mainly in scleroderma and DM-PM [17,18,19] as well as in acute heart-related respiratory events in myocarditis or pericarditis with tamponade [20]. Last but not least, acute antirheumatic drug-related respiratory toxicity as well as acute lung infections related to the ‘mater' disease, specific manifestations of rheumatic disease in the lung, and/or immunosuppressive treatment (including the widespread use of biological factors) complete the spectrum of acute respiratory events in CTDs (table 1) [4,21,22,23,24]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Почти каждый десятый из них (n=1017) имел хотя бы один эпи-зод серьезных инфекций. Суммарно было отмечено 135 случаев сепсиса, ставшего причиной гибели 85 (65%) больных [24].…”
unclassified